Orthodontic Implants: Concepts for the Orthodontic Practitioner - Carlos Nelson Elias; Antônio Carlos de Oliveira Ruellas; Daniel Jogaib Fernandes (Hindawi Limited, 2012)
Orthodontic implants have become a reliable method in orthodontic practice for providing temporary additional anchorage. These devices are useful to control skeletal anchorage in less compliant patients or in cases where absolute anchorage is necessary. There are a great number of advantages in this new approach which include easy insertion, decreased patient discomfort, low price, immediate loading, reduced diameter, versatility in the forces to be used, ease of cleaning, and ease of removal. However, a proper management of the screws by the practitioner is necessary in order to increase the success rate of the technique. The purpose of this paper is to update practitioners on the current concepts of orthodontic implants and orthodontic mechanics.